Direct measurement of fission barrier height of unstable heavy nuclei at ISOL facilities - Veselský, M.; Klimo, J.; Raabe, R.; Andreyev, A. N.; Huyse, M.; Van Duppen, P.; Renzi, F.; Nishio, K.; Makii, H.; Nishinaka, I.; Chiba, S.; Souliotis, G.; et al. (HNPS Advances in Nuclear Physics, 2019)
Fission barrier height is one of the least known nuclear parameters, with experimental data, acquired decades ago, existing only close to beta-stability line. Availability of heavy radioactive beams offers possibility to investigate fission of more exotic nuclei and using the state of the art detection technique such as the active target we can even probe their fission barriers heights with precision has not been reached so far. The present status of fission barrier measurement is going to be explained in this paper. We are going to discuss the possibilities to stage experimental studies of fission barrier heights at new generation of ISOL facilities such as HIE-ISOLDE and active target ACTAR TPC. As an example we select the experiment IS581, being prepared for execution at the HIE-ISOLDE facility (CERN).